Expressions of Matrix Metalloproteinase-7 and -9 and their Prognostic Significances in Rectal Cancer - Cho, Young Rak (Korean Cancer Association, 2005)
PURPOSE: The matrix metalloproteinases (MMPs) are a family of proteolytic enzymes. MMPs are known to be involved in tumor invasion, and several have been implicated in tumor prognosis. The aim of this study was to evaluate the prognostic significances of the expressions of MMP-7 and -9 in rectal cancer. MATERIALS AND METHODS: The tumor tissues of 87 patients with stage II or III rectal carcinoma that underwent potentially curative resection followed by postoperative adjuvant chemoradiation and 5-fluorouracil based chemotherapy, were investigated immunohistochemically using monoclonal antibodies against MMP-7 and MMP-9. Clinical information, including tumor grades, carcinoembryonic antigen (CEA) levels, and disease-free survival and overall survival were evaluated with respect to the expressions of MMP-7 and -9. RESULTS: Median follow-up duration was 53.2 months, and median patient age was 55±11 years (range 32~75). MMP-7 expression in tumor tissue was found to be significantly correlated with the presence of nodal metastasis (p=0.029), whilst MMP-9 expression correlated with depth of tumor invasion (p=0.019). No relationships were found between the expressions of MMP-7 or -9 and age, sex, tumor size, tumor grade, or CEA level. Univariate analysis showed that MMP-7 expression was associated with poor 5-year overall survival (12.8 months vs. 65.3 months, p=0.0405). Multivariate analysis confirmed that MMP-7 was independently associated with an adverse outcome (Relative risk: 1.415, p=0.027). However, MMP-9 expression was not found to be related to clinical outcome. CONCLUSION: MMP-7 expression in tumor tissue is associated with lymph node metastasis and a poor 5-year overall survival in rectal cancer patients.